2006
DOI: 10.1177/105381510602800203
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Community Mentors on Maternal Behaviors and Child Outcomes

Abstract: Play and Learning Strategies (PALS), a research-based parent education and support program, was delivered to families with low income via home visiting using a facilitator. Facilitators completed 12 home visits addressing responsive parenting, behavioral support, language stimulation, and support of attentional skills. This report compares PALS to M-PALS, a program that included a community mentor in addition to a facilitator. Community mentoring provided modeling of parenting skills and supportive services to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“… Abbreviations: S/C, social-communication behaviors; E, emotional behaviors; C, cognitive behaviors; M, mixed outcome; o, observation; s, standardized measures; P, significant positive outcome; N, no significant outcome; *, lower bound of effect size not reported. a Adult outcomes were all measured using observation systems. b Dieterich et al (2006) compared Play and Learning Strategies (PALS) group with M-Play and Learning Strategies (M-PALS) group (which included a community mentor in addition to a facilitator). c Landry et al (2008) consisted of four groups which were PALS I (infancy intervention phase), PALS II (toddler and preschool intervention phase), Developmental Assessment Sessions (DAS I: infancy phase), and DAS II (toddler and preschool phase). …”
Section: Synthesis Resultsmentioning
confidence: 99%
“… Abbreviations: S/C, social-communication behaviors; E, emotional behaviors; C, cognitive behaviors; M, mixed outcome; o, observation; s, standardized measures; P, significant positive outcome; N, no significant outcome; *, lower bound of effect size not reported. a Adult outcomes were all measured using observation systems. b Dieterich et al (2006) compared Play and Learning Strategies (PALS) group with M-Play and Learning Strategies (M-PALS) group (which included a community mentor in addition to a facilitator). c Landry et al (2008) consisted of four groups which were PALS I (infancy intervention phase), PALS II (toddler and preschool intervention phase), Developmental Assessment Sessions (DAS I: infancy phase), and DAS II (toddler and preschool phase). …”
Section: Synthesis Resultsmentioning
confidence: 99%
“…Making sure that very young children have a good amount of exposure to language-literacy stimulating activities in their environment, is, however, important directly to their emergent language. Therefore, providing parental support through home visiting (see recent AAP 2009 recommendations), assuring children's center-based participation in early childhood (or childcare) programs that directly provide children's engagement in such activities (Dietrich et al 2006), and addressing health literacy for child guidance and reduction of health disparities (Sanders et al 2009) are increasingly being recognized as important interventions and policy directives.…”
Section: Discussionmentioning
confidence: 99%
“…Two exceptions are a community-based mentoring program incorporating mentoring into an existing Play and Learning Strategies program (Dieterich et al, 2006) and a multidisciplinary preventative parent mentoring intervention (Zajicek-Farber, 2010). Both studies found women who had a community mentor experienced improvements.…”
Section: Introductionmentioning
confidence: 99%
“…Both studies found women who had a community mentor experienced improvements. For Dieterich et al (2006) this related to increased improvements in interactive behaviours between mothers and their 4 children and gains in children's cognitive development than with mothers who did not have a mentor. For Zajicek-Farber (2010) parents with a mentor experienced improved parenting knowledge and practices, as well as greater maternal resilience and better use of family resources.…”
Section: Introductionmentioning
confidence: 99%